ADAPTIVE MECHANISMS UNDER CONDITIONS OF CONSTANT EXPOSURE TO EXTREME STRESS IN THE CIVILIAN POPULATION - Shumarova, Anastasiia (Modern Psychology, 2024)
The article is dedicated to analyzing the adaptation of civilians under conditions of prolonged and continuous traumatic stress caused by armed conflicts. The relevance of this research stems from the fact that most existing studies focus on the adaptation of soldiers and veterans, leaving a significant gap in understanding how civilians cope with ongoing stress in conflict zones.The article reviews studies examining adaptation and resilience among the civilian population experiencing continuous stress. The literature review confirms that the duration of exposure to traumatic events is a crucial factor in determining the level of adaptation and resilience. It also highlights that prolonged exposure to extreme factors has a cumulative effect on mental well-being, increasing the risk of developing depression, anxiety disorders, and reducing resilience.The article emphasizes the lack of research dedicated to the adaptation of civilians and substantiates the need for further studies in this area. Such research will provide a deeper understanding of adaptation processes under long-term extreme conditions and facilitate the development of effective psychological support programs for civilians living in conflict zones.
Keywords: adaptation; adaptive mechanisms; resilience; stress; armed conflict; civilian population; continuous traumatic stress